Pelatihan Pembuatan Pupuk Organik Cair dari Limbah Kulit Pisang - Masiah Masiah; Ismail Efendi; Siti Nurhidayati; Siti Rabiatul Fajri; Sucika Armiani (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
Environmental problems caused by household waste are issues that are often discussed. Instilling concern for the environment from an early age is very important for all parties, both from the school environment and the surrounding environment at home. This community service activity aims to provide education to MAS Al-Hamidiyah NW Sidemen students, Batu Layar District, West Lombok Regency about how to process organic waste so that it brings high value benefits from what was previously only as waste. The method used in this activity was training related to organic fertilizers, the content of banana peels, as well as demonstrating or practicing the material previously presented, namely on how to make liquid organic fertilizer from banana peels. Based on the results of the activities that have been carried out, it can be concluded that all participants who took part in the training could make their own liquid organic fertilizer, this can be seen from the patientness of the participants when practicing directly step by step the process of making liquid fertilizer.